Fluoride-free synthesis of anodic TiO2 nanotube layers: a promising environmentally friendly method for efficient photocatalysts. Issue 32 (1st August 2022) - Hanif, Muhammad Bilal; Thirunavukkarasu, Guru Karthikeyan; Liapun, Viktoriia; Makarov, Hryhorii; Gregor, Maros; Roch, Tomas; Plecenik, Tomas; Hensel, Karol; Sihor, Marcel; Monfort, Olivier; Motola, Martin
Abstract : TiO2 nanotube (TNT) layers were prepared in fluoride-free nitrate-based electrolytes i.e., NaNO3, KNO3, Sr(NO3 )2, and AgNO3 via electrochemical anodization. Abstract : TiO2 nanotube (TNT) layers are generally prepared in fluoride-based electrolytes via electrochemical anodization that relies on the field-assisted dissolution of Ti metal forming nanoporous/nanotubular structures. However, the usage of fluoride ions is considered hazardous to the environment. Therefore, we present an environmentally friendly synthesis and application of TNT layers prepared in fluoride-free nitrate-based electrolytes. A well-defined nanotubular structure with thickness up to 1.5 μm and an inner tube diameter of ∼55 nm was obtained within 5 min using aqueous X(NO3 )Y electrolytes (X = Na +, K +, Sr 2+, Ag + ). For the first time, we show the photocatalytic performance (using a model organic pollutant), HO˙ radical production, and thorough characterization of TNT layers prepared in such electrolytes. The highest degradation efficiency ( k = 0.0113 min −1 ) and HO˙ radical production rate were obtained using TNT layers prepared in AgNO3 (Ag-NT). The intrinsic properties of Ag-NT such as the valence band maximum of ∼2.9 eV, surface roughness of ∼6 nm, and suitable morphological features and crystal structure were obtained. These results have the potential to pave the way for a more environmentally friendly synthesis of anodic TNT layers in the future using the next generation of fluoride-free nitrate-based electrolytes.